Muhammadiyah in the Dynamics of Ideology: The Battle for Representation Between Islam and Communists in the Dutch East Indies Colony - Rizal, Aslama Nada; Ramadhan, Fauzan Syahru (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
This article examines the position of Muhammadiyah within the dynamics of the relationship between two ideologies, Islam and communism, during the colonial period of the Dutch East Indies, particularly in the 1920s. This period was marked by the emergence of two major ideological forces as a result of the ethical policy: Islam, represented by organizations such as Sarekat Islam (SI) and Muhammadiyah, and communism through the Partai Komunis Indonesia (PKI, Indonesian Communist Party). The aim of this article is to identify and understand the role of Muhammadiyah as an Islamic movement organization in the context of the conflict between Islam and communism during the colonial Dutch East Indies period. This article uses historical methods, including heuristics, source criticism, interpretation, and historiography. The results of this research show that Muhammadiyah was not only involved in this ideological conflict, but also played a significant role in responding to the challenges of communist ideology. Ultimately, this conflict helped shape Muhammadiyah’s character as a more progressive, moderate, democratic Islamic organization that was focused on making real contributions to the struggle for Indonesian independence.